Abnormal market valuation and new product announcements: the role of advancement stage and innovativeness. Issue 2 (3rd April 2018) - Szutowski, Dawid
Abstract: In this paper, I investigate the role of innovativeness and innovation advancement stage with a view to advancing the development of signalling theory within literature on new product announcements. I examine the effects of innovativeness across the eight stages of innovation advancement, applying the event study methodology to a sample of 407 new product announcements, released during the period of January 2011–December 2016 by European biotechnology and pharmaceutical companies. I found that a high level of innovativeness resulted in larger increases of stock market return when the level of advancement was low (during testing phases), and smaller when the production of the new product had commenced. Subsequently, I present practical insights into the role that the advancement stage plays in new product announcements, which may be used to increase market valuation of the firm.